2018
DOI: 10.1002/glia.23542
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between microglia and retinal pigment epithelial cells determines the integrity of outer blood‐retinal barrier in diabetic retinopathy

Abstract: Inner and outer blood‐retinal barriers (BRBs), mainly composed of retinal endothelial cells and retinal pigment epithelial (RPE) cells, respectively, maintain the integrity of the retinal tissues. In this study, we aimed to investigate the mechanisms of the outer BRB disruption regarding the interaction between RPE and microglia. In mice with high‐fat diet‐induced obesity and streptozotocin‐induced hyperglycemia, microglia accumulated on the RPE layer, as in those after intravitreal injection of interleukin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 36 publications
2
79
0
Order By: Relevance
“…In a hyperglycemic environment, several mediators of inflammation contribute to the breakdown of the BRB. In STZ-diabetic mice, the retinal pigment epithelium (RPE) secretes VEGF which in turn triggers the recruitment of microglia to the RPE ( 102 ). Concurrently, microglia-derived TNF-α decreases protein levels of zonula occludens (ZO-1) in RPE cells, thereby disrupting the outer BRB in DR ( 102 ).…”
Section: Breakdown Of the Blood-retina Barrier In Diabetic Retinopathmentioning
confidence: 99%
See 1 more Smart Citation
“…In a hyperglycemic environment, several mediators of inflammation contribute to the breakdown of the BRB. In STZ-diabetic mice, the retinal pigment epithelium (RPE) secretes VEGF which in turn triggers the recruitment of microglia to the RPE ( 102 ). Concurrently, microglia-derived TNF-α decreases protein levels of zonula occludens (ZO-1) in RPE cells, thereby disrupting the outer BRB in DR ( 102 ).…”
Section: Breakdown Of the Blood-retina Barrier In Diabetic Retinopathmentioning
confidence: 99%
“…In STZ-diabetic mice, the retinal pigment epithelium (RPE) secretes VEGF which in turn triggers the recruitment of microglia to the RPE ( 102 ). Concurrently, microglia-derived TNF-α decreases protein levels of zonula occludens (ZO-1) in RPE cells, thereby disrupting the outer BRB in DR ( 102 ). Likewise, BRB breakdown was prevented in TNF-α knockout rats after six months of STZ induced diabetes implying that TNFα plays an important role in BRB disruption ( 103 ).…”
Section: Breakdown Of the Blood-retina Barrier In Diabetic Retinopathmentioning
confidence: 99%
“…But over time, it disrupts the outer blood-retinal barriers (BRB) and acts as a pathologic angiogenic stimulus. 77,78 These studies indicate the feasibility of CDDP against DR by targeting these predicted targets and their biological processes. Our results showed that CDDP might regulate multiple targets of DR, including in ammatory cytokines and growth factors et al…”
Section: Discussionmentioning
confidence: 89%
“…The results showed that the common targets were mainly concentrated in the advanced glycation end-products and receptor for advanced glycation end-products (AGE-RAGE) signaling pathway, uid shear stress and atherosclerosis, apoptosis, tumor necrosis factor (TNF), hypoxia-inducible factor-1 (HIF-1), phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) and VEGF signaling pathway, which regulate many biological processes like oxidative stress, blood pressure, hemodynamic change, apoptosis, in ammation, retinal ischemia, proliferation and differentiation. [19][20][21][22][23][24][25][26]…”
Section: Go and Kegg Enrichment Analysismentioning
confidence: 99%
“…These initial studies have been expanded to investigate the cross-talk between RPE and microglia. Jo and associated demonstrated that interaction between these cells determines the integrity of the outer blood-retinal barrier in murine diabetic retinopathy [44]. This interaction was mediated by the presence of IL-6 and the production of TNF-α by the microglia cells.…”
Section: Rpe Cell and Microglia Interactionsmentioning
confidence: 97%